MORPHOLOGY AND HABITS OF Langsdorfia sp. PASSION FRUIT SWEEPER IN THE CAUCA VALLEY - R. DE HERNÁNDEZ, ANGELA MARTHA; CHACÓN, PATRICIA (Revista Colombiana de Entomología, 1979)
The "Maracuya" crop (Passiflora edulis f. flavicarpa) has become one of the most important sources of income for the farmers of the Santa Elena area (Cerrito Country) in the Cauca Valley (West of Colombia). Fruit productivity has declined due to the presence of Lepidoptera larvae which bore roots, crown, and stems causing sizeable holes in young (less than one year of age) as well as in older vi ones. An average of fifteen larvae per plant was found at different instars. The species was identified as Langsdorfia sp. (Cossidae). Other species from this family have been reported to attack fruit trees. However, there is no reported evidence of damage caused by them on "Maracuya". This study describes the morphology of different instar of the larva, the life cycle, feeding habits, and type of damage. In addition, some control strategies are proposed.